SYSTEMATIC LITERATURE REVIEW: THE INFLUENCE OF LEADERSHIP STYLE ON EMPLOYEE ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Jannah, Alfina Nur; Zagladi, Arief Noviarkahman; Nora, Elfia (PT. Media Edutama Nusantara, 2025)
Organizational Citizenship Behavior (OCB) refers to employees’ discretionary behaviors that go beyond formal job requirements and contribute significantly to organizational effectiveness and sustainability. In increasingly dynamic and competitive work environments, leadership style has become a critical factor in fostering such extra-role behaviors. This study aims to systematically review empirical research examining the influence of leadership styles on Organizational Citizenship Behavior (OCB). A Systematic Literature Review (SLR) approach was employed, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to ensure a transparent and rigorous review process. Articles were retrieved from reputable scientific databases and screened using strict inclusion and exclusion criteria. As a result, 33 empirical studies published between 2010 and 2025 were selected for in-depth analysis. The findings indicate that transformational leadership is the most dominant and consistently influential leadership style in promoting OCB across various organizational contexts. However, its effects are generally indirect and mediated by psychological and organizational factors such as affective commitment, work engagement, trust, job satisfaction, and organizational culture. In addition, servant, ethical, authentic, inclusive, and responsible leadership styles also demonstrate positive relationships with OCB, although their effects tend to be contextual and dependent on specific mediating mechanisms. In contrast, transactional leadership exhibits mixed and inconsistent findings regarding its impact on OCB. These results highlight that the relationship between leadership styles and OCB is complex and multidimensional rather than linear. This study contributes to the literature by mapping research trends, synthesizing key mediating mechanisms, and identifying gaps for future research. Practically, the findings provide valuable insights for organizations in designing leadership development strategies aimed at fostering employees’ Organizational Citizenship Behavior in a sustainable manner.